Self-powered illuminating glucose sensor. (15th December 2022) - Jin, Huding; Lee, Won Hyung; Cho, Yong Hyun; Han, Junghyup; Im, Changik; Yu, Seungyeon; Li, Lianghui; Lee, Jaewon; Yin, Zhenxing; Kim, Youn Sang
Abstract: Nowadays, the development of various electricity generation methods via dynamic water motions has been intensively focused on. While verifying the exact electricity generation mechanism, another important task of making full use of the electricity generated by the solid-liquid interaction is being considered. Herein, we demonstrated a self-powered illuminating glucose sensor with high sensitivity (∼ 22.61 V·M −1 ) and selectivity, and a wide detection range (0.5–100 mM), utilizing the electricity generated from the water infiltration into a glycine-coated porous CuO nanowires film. Fundamentally, the sensing mechanism could be comprehensively verified by an ionovoltaic effect that attributes the electricity generation to the adsorption/desorption of ions or protons at the solid-liquid interface. As the concentration of adsorbed glucose increases, the generated open-circuit voltage decreases accordingly. Moreover, by selectively turning on LEDs with different threshold voltages, the glucose concentration that is harmful to the human body is successfully distinguished. Overall, the self-powered illuminating sensor platform utilizing electricity generated by the water-infiltration phenomenon provides the feasibility of novel biosensors. Graphical Abstract: A self-powered illuminating glucose sensor with high sensitivity (∼ 22.61 V·M −1 ) and selectivity, and a wide detection range (0.5–100 mM), through water infiltration phenomenon utilizing a glycine-coated porous CuO nanowires film (G-PCNF), was demonstrated. The complex phenomena at the solid-liquid interface, such as the influence of adsorption/desorption of ions and specific binding of glucose molecules on the electricity generation, were comprehensively verified by the ionovoltaic effect. When the adsorbed glucose concentration increased, the adsorbed hydroxide ions on the G-PCNF surface decreased, which caused a reduction in carrier concentration difference between the wet and dry region of the G-PCNF, and the generated open-circuit voltage ( V oc ) became smaller. ga1 Highlights: A self-powered illuminating glucose sensor (glycine-coated porous CuO nanowires film) utilizing electricity generated from the water-infiltration phenomenon was demonstrated. The glycine-coated porous CuO nanowires film could selectively bind with glucose molecules. The relationship between electricity generation and the concentration of glucose molecules was thoroughly verified by the ionovoltaic effect .